2019
DOI: 10.3389/fpsyg.2019.01505
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Structure and Cultural Invariance of DSM V Post-traumatic Stress Disorder Among Iraqi and Syrian Displaced People

Abstract: While the factor structure of post-traumatic stress disorder (PTSD) symptoms has been investigated among various traumatized populations in Western and high-income countries, knowledge regarding the validity of factor structure of PTSD among culturally diverse populations in low-and-middle-income countries is limited. The current study examined the factor structure and cultural invariance of PTSD in 521 Iraqi and 993 Syrian war-affected displaced people who were living in the Kurdistan Region of Iraq. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
(87 reference statements)
2
20
0
Order By: Relevance
“…A detailed description of the data collection procedure is described in detail elsewhere (e.g. Ibrahim, Catani, Ismail, & Neuner, 2019 ; Ibrahim, Ertl, Catani, Ismail, & Neuner, 2018a ). Participants with no trauma exposure history and who were under the age of 18 were excluded from analyses, leading to a sample of N = 974 participants included in the analyses (N = 494 males and N = 480 females).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the data collection procedure is described in detail elsewhere (e.g. Ibrahim, Catani, Ismail, & Neuner, 2019 ; Ibrahim, Ertl, Catani, Ismail, & Neuner, 2018a ). Participants with no trauma exposure history and who were under the age of 18 were excluded from analyses, leading to a sample of N = 974 participants included in the analyses (N = 494 males and N = 480 females).…”
Section: Methodsmentioning
confidence: 99%
“…Adverse and traumatic life events were evaluated by applying the War and Adversity Exposure Checklist (Ibrahim et al, 2018a ) comprising 25 potential traumatic events. Current PTSD symptoms were assessed by valid and reliable Arabic and Kurdish versions of the PTSD Checklist for DSM-5 (PCL-5) (Ibrahim et al, 2019 ). To determine probable PTSD diagnosis, the cut-off score of 23 or higher of the PCL-5 was used as suggested in a recent validation study in the same cultural context (Ibrahim, Ertl, Catani, Ismail, & Neuner, 2018b ).…”
Section: Methodsmentioning
confidence: 99%
“…40 The instrument had been translated, culturally adapted, and validated among Iraqi and Syrian displaced people, including Yazidis. 41,42 Scores on the PCL-5 scores range from 0 to 80.…”
Section: Mental Healthmentioning
confidence: 99%
“…Surveys conducted in other war-affected and low-income regions found that prevalence rates of DSM-IV PTSD were, e.g. 37% in Algeria in a sample of survivors of armed conflict, 28% in Cambodia in samples from three selective areas surveying refugee camp returnees, poor population facing continues civil strife and a sample from the capital with a relatively higher living-standard, 18% in refugee camps, cities, and resettlement areas of Gaza, and 16% in Ethiopia in a sample of registered refugees and up to 64% in a sample of Iraqi displaced individuals (de Jong et al, 2001 ; Ibrahim, Catani, Ismail, & Neuner, 2019 ). Both the individual well-being and functioning as well as the development of a peaceful post-war society require effective treatments for individuals with multiple traumatization suffering from PTSD.…”
Section: Introductionmentioning
confidence: 99%